PERSPEKTIF FIQH MUAMALAH TERHADAP TRANSAKSI JUAL BELI UANG RUSAK DI PASAR KOTABUMI LAMPUNG - Edi Mulyono (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
Abstract: There are various kinds of buying and selling problems in the community, such as buying and selling damaged money, of course this transaction violates Article 22 of Law Number 7 of 2011 concerning Currency, which states that a sufficient nominal amount, appropriate denominations, and conditions suitable for circulation are indispensable for meet the demand for Rupiah money in society. This type of research is field research with a descriptive qualitative approach. Primary and secondary data are used as data sources, and interviews, observation, and documentation are used as data collection methods. Tend to reason that contracts in buying and selling and obtaining damaged money at Pasar Kotabumi Lampung cannot be classified as service providers, arguing that during the exchange there is no service contract (ujrah) from one or two sellers who initiate that the exchange is an exchange of cash trading administration aggrieved, where one of the circumstances is how much wages are known by the two actors. Therefore, this practice is included in the buying and selling of currency (al-sharf) but cannot be considered as an exchange service. The muamalah fiqh perspective on determining the exchange rate of damaged money and the criteria for money that can be traded at the Kotabumi Market in Lampung is followed by the practice of buying and selling damaged money, namely buying and selling between damaged money and normal money in terms of differences. quality and ilat as legal tender. Due to an imbalance in nominal exchange rates, this type of buying and selling currency (al-sharf) from the perspective of muamalah fiqh does not meet the legal requirements of buying and selling al-sharf, as a result this transaction contains elements of usury.